The Effect Of Workload, Work Motivation And Work Discipline On Civil Servant Performance During Remote Working Period - Syakur, Nadyasyifa Annisa; Rialmi, Zackharia (Journal of Applied Management and Business, 2025)
This research is a quantitative research, the purpose of this research is to know the influence of workload, motivation and work discipline on employee performance in the field of utilization division of center for data and information at ministry of education and culture Republic of Indonesia, during the implementation of Remote working. This study used a sample of 65 employees using saturated sample techniques. Data analysis techniques used in this study is partial least square (PLS). Test results obtained in this study first, workload positively and significantly affect the performance of employees in the field of utilization division of center for data and information at ministry of education and culture during remote working. Second, motivation positively and significantly affect the performance of employees in the field of utilization division of center for data and information.